2019
DOI: 10.1038/s41598-019-38534-6
|View full text |Cite
|
Sign up to set email alerts
|

Niraparib activates interferon signaling and potentiates anti-PD-1 antibody efficacy in tumor models

Abstract: PARP inhibitors have been proven clinically efficacious in platinum-responsive ovarian cancer regardless of BRCA1/2 status and in breast cancers with germline BRCA1/2 mutation. However, resistance to PARP inhibitors may preexist or evolve during treatment in many cancer types and may be overcome by combining PARP inhibitors with other therapies, such as immune checkpoint inhibitors, which confer durable responses and are rapidly becoming the standard of care for multiple tumor types. This study investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(140 citation statements)
references
References 55 publications
5
132
1
2
Order By: Relevance
“…Although the result of an early phase II clinical trial combining Durvalumab with Olaparib in patients with relapsed small cell lung cancer did not meet the preset bar for efficacy [93], we are awaiting the results of ongoing clinical trials to better judge their effectiveness. Moreover, the PARP inhibitor Niraparib has been shown to enhance type I interferon signaling and T cell infiltration in the tumor and improve the therapeutic effect of anti-PD-1 [94]. NK cells can kill cancer cells by inducing death receptor-mediated apoptosis through the expression of FasL or TRAIL [71].…”
Section: Parp Inhibitors As Immunomodulatory Agentsmentioning
confidence: 99%
“…Although the result of an early phase II clinical trial combining Durvalumab with Olaparib in patients with relapsed small cell lung cancer did not meet the preset bar for efficacy [93], we are awaiting the results of ongoing clinical trials to better judge their effectiveness. Moreover, the PARP inhibitor Niraparib has been shown to enhance type I interferon signaling and T cell infiltration in the tumor and improve the therapeutic effect of anti-PD-1 [94]. NK cells can kill cancer cells by inducing death receptor-mediated apoptosis through the expression of FasL or TRAIL [71].…”
Section: Parp Inhibitors As Immunomodulatory Agentsmentioning
confidence: 99%
“…Interestingly, synergistic anti-tumor activity of niraparib and PD-1 blockade was seen in both BRCA-deficient and BRCA-proficient immunocompetent tumor models indicating that this combination may be active regardless of BRCA status. Furthermore, mice in complete remission after treatment rejected implanted tumor cells indicating the generation of memory T-cells [94]. Preclinical studies have shown that DSBs leads to upregulation of PD-L1 expression through ATM/ATR/Chk-1.…”
Section: Parpi In Combination With Immunotherapymentioning
confidence: 99%
“…However, there is hope for increased response rates through patient selection and combination of therapies. For example, there is emerging preclinical data suggesting that the patient population that responds to PARP inhibition and PD-1/PD-L1 antibodies may significantly overlap [9], and it is hypothesized that increased DNA damage by PARP inhibition will increase the number of tumor neoantigens, creating a more antigenic environment in which to stimulate the immune microenvironment [10]. Thus, development of predictive biomarkers is needed to identify the subset of patients who will benefit from treatment and to minimize the risk of toxicities.…”
Section: Introductionmentioning
confidence: 99%